Associations of mid-childhood bisphenol A and bisphenol S exposure with mid-childhood and adolescent obesity. Issue 1 (20th February 2022) - Gajjar, Priya; Liu, Yun; Li, Nan; Buckley, Jessie P.; Chen, Aimin; Lanphear, Bruce P.; Kalkwarf, Heidi J.; Cecil, Kim M.; Yolton, Kimberly; Braun, Joseph M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Bisphenol A (BPA) is a suspected obesogen that has been associated with adiposity in children. Bisphenol S (BPS), a structural analog of BPA, is used as a BPA substitute and may have similar health effects as BPA. However, few studies have examined whether BPS is associated with childhood adiposity. Methods: We quantified urinary BPA and BPS concentrations in 212 children age 8 years from the HOME Study, a prospective pregnancy and birth cohort study that enrolled pregnant women in Cincinnati, Ohio (2003–2006). We assessed children's adiposity by bioelectric impedance at age 8 years (n = 212), and by anthropometry and dual-energy X-ray absorptiometry at age 12 years (n = 181). We measured serum adipocytokine concentrations at age 12 years (n = 155). Using multivariable linear regression, we estimated covariate-adjusted associations of BPA and BPS with adiposity measures at ages 8 and 12 years and adipocytokine concentrations at age 12 years. Results: Each 10-fold increase in urinary BPA concentrations were inversely associated with percent body fat at age 8 years [β = −1.2, 95% confidence interval (CI) = −3.4, 1.0] and 12 years (β = −1.6, 95% CI = −4.0, 0.9). In contrast, urinary BPS concentrations were positively associated with percent body fat at age 8 years (β = 1.1, 95% CI = −0.6, 2.7), but not at 12 years (β = 0.1, 95% CI = −1.7, 1.8). Urinary BPA and BPS concentrations were not associated with serum adiponectin or leptin concentrations. Conclusions: We did not observe evidence that urinary BPA or BPS concentrations during childhood were associated with greater child adiposity at ages 8 and 12 years in this cohort.